MEMAHAMI 5 SHALAT SUNAH RASULULLAH DALAM FIKIH IBADAH MENURUT AL-MUZANI - Nafidatun Nisa; Ulfatussyarifah; Miss Fatihah Saman; Lutfiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study discusses five sunnah prayers recommended by the Prophet PBUH from the perspective of worship fiqh according to Al-Muzani, namely the Witir prayer, the prayer before Fajr, the Eid al-Fitr and Eid al-Adha prayers, the solar and lunar eclipse prayers, and the Istisqa prayer. These five prayers have a special position in Islam because they are recommended by the Prophet Muhammad PBUH which is explained in various fiqh literature such as sahih hadiths which are believed to be authentic. This study aims to understand the importance of carrying out the five sunnah prayers of the Prophet, namely the Witir prayer, the prayer before Fajr, the Eid al-Fitr and Eid al-Adha prayers, the solar and lunar eclipse prayers, and the Istisqa prayer. The research method used in this study is the library research method, this study discusses the importance of carrying out sunnah prayers as a complement of worship that must be supported by sahih hadiths that are believed to be authentic. The results of the study show that by understanding and practicing these five sunnah prayers, a Muslim can improve the quality of his worship and strengthen the relationship with Allah SWT and others.